Biomarkers of Environmental Enteric Dysfuction and Associations with Child Linear Growth in Rural Odisha, India (OR10-06-19) - Sinharoy, Sheela (Curr Dev Nutr, 2019)
OBJECTIVES: Intestinal dysfunction due to mucosal inflammation, known as environmental enteric dysfunction (EED), has been hypothesized to contribute to stunting in low- and middle-income countries (LMICs). Given that consensus is lacking on gold standard biomarkers for EED and on relationships with child linear growth, we examined three biomarkers of EED and height-for-age z-score (HAZ) among children under age five years in rural Odisha, India. METHODS: We conducted a sub-study within Gram Vikas MANTRA, a matched cohort study of a household-level water and sanitation intervention in Odisha, India. We collected stool samples and anthropometry data for children under age 5 (N = 209) in two rounds (October 2016 – January 2017 and July – October 2017). We analyzed stool samples for three biomarkers of EED: myeloperoxidase (MPO), neopterin (NEO), and α1-anti-trypsin (AAT). We assessed correlations between values and used linear regression to analyze associations between each biomarker and HAZ. All analyses were adjusted for relevant covariates and village-level clustering. RESULTS: Mean HAZ for children under 5 in our sample population was -1.52 (SD: 1.34). Median biomarker values (25th, 75th percentiles) were 1052.71 ng/ml (682.76, 3208.22) for MPO, 2104.21 nmol/L (1193.64, 3490.10) for NEO, and 0.406 mg/g (229.44, 743.78) for AAT. Correlations between the biomarkers were relatively low, with the highest correlation (ρ = 0.45) between MPO and AAT. We observed an inverse association between MPO and HAZ (β = -0.000027, P < 0.001) but no association between NEO and HAZ (β = 0.000031, P = 0.46) or AAT and HAZ (β = -0.000072, P = 0.52). CONCLUSIONS: In our sample population, median values for NEO and AAT were similar to those from other studies of children in LMICs. MPO had substantially lower values than in other reports but was still strongly associated with HAZ. Previous studies have produced conflicting evidence on relationships between each biomarker of EED and HAZ. Our results contribute evidence that intestinal inflammation may play an important role in growth faltering in young children, possibly through mucosal dysfunction. MPO is a major component of the primary granules in neutrophils and hence reflects luminal neutrophillic infiltration. Priorities for a future research agenda on EED and growth will be discussed. FUNDING SOURCES: Bill and Melinda Gates Foundation.